Analisis Pemahaman Konsep dan Kebutuhan Strategi Pembelajaran Berdiferensiasi dengan Multi-Representasi: Studi Empiris Dinamika Partikel 1 Dimensi - Muhammad Reyza Arief Taqwa; Parlindungan Sinaga; Rahmania Amanah Putri; Amira Setiyani; Shinta Nuriyah Mahbubiyah Royani; Siti Jamiatul Husnaini (Universitas Garut, 2026)
Weak conceptual understanding of particle dynamics and the lack of accommodation for students' diverse learning styles are fundamental problems in Classical Mechanics lectures. This mixed-methods study with an explanatory sequential design aimed to analyze the level of conceptual understanding, learning style profiles, and the need for a differentiated instruction strategy based on multi-representation on the topic of 1-Dimensional Particle Dynamics. The subjects were 217 students from two study programs in East Java, from whom 20 students were purposively selected for open-ended questionnaires and interviews. The results showed a low average conceptual understanding score (42.52) with large variation (SD = 19.70), and persistent conceptual difficulties were identified through interviews, particularly in understanding forces, free-body diagrams, and kinematic graphs. The learning style profile revealed a balance between unimodal (50.24%, dominated by visual at 21.20%) and multimodal (49.76%). Students reported the greatest difficulties in understanding forces and free-body diagrams (90%) and graph interpretation (85%). The most preferred representational formats were animation/simulation (40%) and live demonstration (30%). Eighty percent of students expected multi-format learning materials, and students with low scores specifically requested individual feedback. These findings collectively indicate that a differentiated instruction strategy integrating multi-representation is needed, with variation in representational formats, active participation opportunities, and connections to students' concrete everyday experiences as its key design principles.